2021
DOI: 10.1021/acsnano.0c09248
|View full text |Cite
|
Sign up to set email alerts
|

Overscreening, Co-Ion-Dominated Electroosmosis, and Electric Field Strength Mediated Flow Reversal in Polyelectrolyte Brush Functionalized Nanochannels

Abstract: Controlling the direction and strength of nanofluidic electrohydrodyanmic transport in the presence of an externally applied electric field is extremely important in a number of nanotechnological applications. Here, we employ allatom molecular dynamics simulations to discover the possibility of changing the direction of electroosmotic (EOS) liquid flows by merely changing the electric field strength in a nanochannel functionalized with polyelectrolyte (PE) brushes. In exploring this, we have uncovered three fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 72 publications
3
41
1
Order By: Relevance
“…Such OS results in a highly nontrivial distribution of the mobile ions inside the nanochannel with an excess of co-ions or Cl – ions (relative to counterions or Na + ions) inside the brush-free bulk. Such an excess of co-ions in the brush-free bulk, coupled with a very weak flow strength inside the brush layer, had led to a co-ion-dominated EOS flow in the presence of low to medium electric fields, as revealed by our previous study . However, for the present case, the streaming current, caused by the left-to-right pressure-driven advection of the net charge density of the EDL induced by the charged brushes is counterion-driven (i.e., driven by the migration of the Na + ions).…”
supporting
confidence: 42%
See 2 more Smart Citations
“…Such OS results in a highly nontrivial distribution of the mobile ions inside the nanochannel with an excess of co-ions or Cl – ions (relative to counterions or Na + ions) inside the brush-free bulk. Such an excess of co-ions in the brush-free bulk, coupled with a very weak flow strength inside the brush layer, had led to a co-ion-dominated EOS flow in the presence of low to medium electric fields, as revealed by our previous study . However, for the present case, the streaming current, caused by the left-to-right pressure-driven advection of the net charge density of the EDL induced by the charged brushes is counterion-driven (i.e., driven by the migration of the Na + ions).…”
supporting
confidence: 42%
“…Unlike the traditionally used continuum models that always predict a counterion dominated streaming current, it is difficult to predict the direction of streaming current in our system due to the presence of the OS. Our previous study has established that the OS-dictated ion distribution leads to the onset of a co-ion-driven EOS transport . This originates from the fact that there is little flow (due to the large drag) inside the PE brush layer, while there is an excess of co-ions in the brush-free bulk: as a result, the net motion of the water is toward the direction of migration of the co-ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al 49 studied the EOF through nanochannels with polymer patterning surfaces by MD simulations and observed that the polymer patterning induced anisotropy of the EOF when the direction of the electric field was changed. In a recent work, Das and co-workers 50 studied the EOF through nanochannels functionalized with PE brushes by all-atom MD simulations and observed that the direction of the EOF changed by changing the electric field strength.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the study of molecular interactions is a shared and fundamental interest in seemingly unrelated fields, such as biophysics 1 and adhesion, 2 corrosion science, 3 and stem cell research, 4 or electro-osmosis in ion channels. 5 In essence, competing molecular interactions, such as competitions of different specific and unspecific bonds, drive subtle molecular balances and equilibria in the complex machinery of life and in technology.…”
Section: Introductionmentioning
confidence: 99%